Pengaruh Penambahan Arang Pelepah Sawit terhadap Sifat Mekanik Batu Bata Merah - Cory Dian Alfarisi; Padil Padil; Drastinawati Drastinawati; Wisrayetti Wisrayetti; Nurfatihayati Nurfatihayati; Yelmida A (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
Brick is a building material that is often used for residential walls. The bricks in this study were bricks with the addition of palm frond charcoal in the manufacturing process. The aims of this study were (1) to determine the effect of adding palm stem charcoal on the manufacture of red bricks in terms of compressive strength, water absorption (Suction rate) and apparent density (apparent density). (2) Comparing the test results with the SNI 15-2094-2000 standard. The manufacture of experimental bricks begins with adding clay with pulverized palm frond charcoal in a ratio of 100:0, 95:5, 90:10, 85:15 and 80:20, then molded, dried, burned and tested for new mechanical properties. brick. In this study, the compressive strength of bricks that enter class 100 is a ratio of 100:0 and 95:5 namely 11.75 Mpa and 10.10 Mpa, then bricks grade 50 is a ratio of 90:10 and 85:15 which is 8.08 Mpa and 6.27 Mpa. The water absorption capacity of bricks that meet the requirements of SNI 15-2094-2000 is a ratio of 100:0 and 95:5, namely 18.65% and 19.74%. The apparent density of bricks that meet the requirements of SNI 15-2094-2000 are the ratios of 100:0, 95:5, 90:10 and 85:15, which are 1.63 g/cm3, 1.54 g/cm3, 1,37 g/cm3 and 1.24 g/cm3. Bricks that meet the standards and are recommended as masonry bricks are bricks with a ratio of 95:5.